Importin-α Promotes Passage through the Nuclear Pore Complex of Human Immunodeficiency Virus Type 1 Vpr - Kamata, Masakazu (American Society for Microbiology, 2005)
Viral protein R (Vpr) of human immunodeficiency virus type 1 has potent karyophilic properties, but details of the mechanism by which it enters the nucleus remain to be clarified. We reported previously that two regions, located between residues 17 and 34 (αH1) and between residues 46 and 74 (αH2), are indispensable for the nuclear localization of Vpr. Here, we reveal that a chimeric protein composed of the nuclear localization signal of Vpr, glutathione S-transferase, and green fluorescent protein was localized at the nuclear envelope and then entered the nucleus upon addition of importin-α. An in vitro transport assay using a series of derivatives of importin-α demonstrated that the carboxyl terminus was required for this nuclear import process. We also showed that Vpr interacts with importin-α through αH1 and αH2; only the interaction via αH1 is indispensable for the nuclear entry of Vpr. These observations indicate that importin-α functions as a mediator for the nuclear entry of Vpr.